KESIAPAN KERJA SISWA JURUSAN TATA KECANTIKAN KULIT SMK NEGERI 6 PADANG DALAM MELAKSANAKAN PRAKTIK KERJA INDUSTRI (PRAKERIN) - Mardani, Nuzra; Rostamailis, Rostamailis; Hayatunnufus, Hayatunnufus (Journal of Home Economics and Tourism, 2017)
The background of this study is the problems that indicate a lack of job readiness of students in implementing field Industrial practice; it can be seen from the students who will carry out feel awkward and afraid of the task given. Incomprehension students about the correction of facial for example the presence of facial skin disorders such as acne, the students hard and do not understand how to take care of the client's face. There is a lack of knowledge of students about the procedure of the body or facial skin care. This study aims to reveal the students' job readiness Governance Skin Beauty Department of SMK Negeri 6 Padang in implementing the industry work practices (Prakerin) assessed the readiness of cognitive and psychomotor readiness.This type of research is descriptive quantitative. The populations in this study were students in grade X and XI SMK Negeri 6 Padang enrolled in the Academic Year 2016/2017 Governance Skin Beauty Department with the number 56 of the total sampling. Data collection techniques for data use test cognitive or psychomotor problems and to the data using a questionnaire in the form of Likert scale.Based on the result, students' job readiness in implementing Prakerin, preparedness knowledge (cognitive) obtained the degree of achievement of 62.02% of respondents with a low category of student governance skin beauty. On the job readiness of students in performing Prakerin based readiness skills (psychomotor) is the percentage of 65.26% with a medium category, a description of each sub indicators that mimic the percentage of 67.00%, 67.14% manipulation, motion fidelity 63.75 %, the articulation of 64.93% and 63.13% naturalization. From the research results can be recommended for the parties concerned to work could further enhance the readiness of students to be ready to enter the working world.Keywords: Readiness Student Work, Employment Practices Industry